Extraction of petroleum emulsified water and characterization of major ions for the evaluation of its origin. (1st December 2017) - Teixeira, Heloisa Maria Fontenelle; Duyck, Christiane; do Rosário, Francisca Ferreira; Bezerra, Maria Carmem Moreira; Rocha, Anderson Araujo; da Fonseca, Teresa Cristina Oliveira; Saint'Pierre, Tatiana Dillenburg; Miekeley, Norbert
Graphical abstract: Highlights: A method for the direct extraction of petroleum emulsified water was developed. The method was adequate to w/o emulsions higher than 0.1%, in viscous oils. Cations were determined by ICP OES and anions by ion chromatography. The emulsified water origin was evaluated by ions versus [Cl − ] distributions. The results were employed to identify scale formation potential. Abstract: A method for the extraction of emulsified water associated with crude oil was developed, in order to determine the composition of its major cations by inductively coupled plasma optical emission spectrometry (ICP OES) and anions by ion chromatography (IC). The method is suitable to crude oils with water content as low as 0.4% (w/w) and the recovery of elements was satisfactory (80–115%), except in the case of Ba 2+, possibly due to the presence of insoluble BaSO4 in the crude oils. Concentrations of dissolved Na +, Cl −, Ca 2+ and Sr 2+ show good agreement in interlaboratory results of three crude oils and between replicates (0.05–16%), whereas SO4 2− and Ba 2+ results were more scattered. The emulsified waters had contributions of formation and injection waters and these were reflected in their ions distributions. In the 30 crude oil samples investigated, NaCl was the predominant salt and the correlations of Br −, Ca 2+ and Sr 2+ concentrations to Cl − concentration showed low values, indicating that the origin of the dissolved ions was through dissolution of halite by rock buffering processes. The contribution of injection and formation waters was observed in the [Br − ] versus [Cl − ] plot and the potential of scale formation is discussed through log correlation of [Ba 2+ ] versus [SO4 2− ]. The overall method is fast and does not require the use of a time consuming reactor, making it a good one for a first evaluation of the aqueous phase composition during petroleum exploration and production.